Listening to Chinese Immigrant Restaurant Workers in the Midwest: Application of the Culture-Centered Approach (CCA) to Explore Perceptions of Health and Health Care. Issue 6 (2nd June 2016) - Gao, Haijuan; Dutta, Mohan; Okoror, Titilayo
ABSTRACT: This study engages with the culture-centered approach (CCA) to explore Chinese immigrant restaurant workers' perception of the U.S. health care system and their interactions with the health care system in interpreting meanings of health. Chinese restaurant workers are marginalized because of their struggles on the job, their immigrant identity, and their negotiations with the structural contexts of occupation, migration status, and culture. In-depth interviews were conducted with 18 Chinese immigrant restaurant workers that lasted an average of 1.5 hours each, and were audiotaped. Interviews with participants highlighted critical issues in access to health care and the struggles experienced by restaurant workers in securing access to health, understood in the context of work. Critical to the workers' discourse is the acknowledgment of structural constraints such as lack of insurance coverage, immigration status, and lack of understanding of how the U.S. health care system works.